Produksi Tanaman Okra (Abelmoschus esculentus L. Moench) Akibat Aplikasi Mikoriza dan Pupuk Rock Phosphat pada Cekaman Salin - Mizan Maulana; Vinny Pratiwi; Rika Yusli Harta; Zaitun Ritaqwin; Darmadi Erwin Harahap (Institut Pertanian Bogor, 2024)
Okra (Abelmochus esculentus L. Moench) has a fairly high nutritional content; every 10 gr of young okra fruit contains 33 calories, 7 gs of carbohydrates, 3.2 gs of fiber, and 81 mg calcium. Okra fruit contains a lot of mucilage due to its high fiber content. This study aimed to determine the effect of rock phosphate doses and types of mycorrhizae and the interaction between these two factors on the growth and yield of okra in saline soil. The research results showed that the dose of mycorrhiza had a very significant effect on the growth and yield of okra plants. The best dose of mycorrhiza was 10 g/plant, and the best type was Acauluspora. It showed that a dose of 10 g/plant with the Acauluspora type on okra yields on Ultiisol soil had given the best results in the vegetative phase, which could be seen in plant height parameters 15 and 30 ADP. The dose of rock phosphate is 150 g, which can be seen in the 300 g planting parameter and in almost all the observed variables. Hyphae in the soil can spread widely, which helps absorb more water. The best yields of okra plants were found by applying a mycorrhizal dose of 10 g on fruit weight variables of plants' mycorrhizal colonization on vase vegetative roots and mycorrhizal colonization on plant roots in the generative phase. Keywords: biological agents, fertilizer, mycorrhiza, rock phosphate